2007
DOI: 10.1016/j.pec.2006.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary counseling and testing among post-partum women in Botswana

Abstract: Objective-To determine uptake and socio-demographics predictors of acceptance of voluntary counseling and testing (VCT) among post-partum women in Botswana.Methods-Women attending maternal and child health clinics for their first post-partum or well baby visit in 3 sites in Botswana were offered VCT after a written informed consent. A standardized questionnaire was used to collect socio-demographic characteristics and reasons for declining VCT.Results-From March 1999 to November 2000, we approached 1735 post-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 20 publications
3
16
0
Order By: Relevance
“…Associations between HIV test refusal and age, education and marital status have been reported previously (Mpairwe et al. 2005; Thior et al. 2007).…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…Associations between HIV test refusal and age, education and marital status have been reported previously (Mpairwe et al. 2005; Thior et al. 2007).…”
Section: Discussionsupporting
confidence: 56%
“…Similarly conflicting associations with VCT uptake rates have been reported in relation to marriage for women (Matovu et al. 2005; Thior et al. 2007).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Population-based studies undertaken in the same countries revealed that the percentages of women and men living with HIV who knew their HIV sero-positive status were 12-25% and 8-24%, respectively (WHO ⁄ UNAIDS ⁄ UNICEF 2007). Traditional VCT-related barriers, such as low perceived risk for HIV infection and lack of access to free testing (Nakanjako et al 2006), general negative perceptions of test services, stigmatizing beliefs coupled with fear of discrimination (Kalichman & Simbayi 2003), a shortage of counsellors, concerns about confidentiality and delays in returning HIV test results (Creek et al 2007) continue to hamper effective access to and uptake of VCT in many sub-Saharan African countries (Kalichman & Simbayi 2003;Urassa et al 2005;Marum et al 2006;Thior et al 2006;Yoder et al 2006;Creek et al 2007).…”
Section: Introductionmentioning
confidence: 99%